2017
DOI: 10.4314/ahs.v16i4.37
|View full text |Cite
|
Sign up to set email alerts
|

Locally manufactured wheelchairs in Tanzania – are users satisfied?

Abstract: Background: The government of Tanzania created opportunity for the production of wheelchairs that would be appropriate to the local needs and environment. Objectives: The study assessed the extent to which the wheelchairs met the activity and participation needs of the users, as well as the users' level of satisfaction with the provision, repair and maintenance of these wheelchairs. Methods: A descriptive cross-sectional analytical design was utilized to collect data through the administration of a questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
2
3
0
3
Order By: Relevance
“…Another similarity was female users being more satisfied with the wheelchair compared to men. In Tanzania the reported satisfaction levels with locally manufactured wheelchairs were higher compared to this study where customized wheelchairs were provided that can be contributed to the poor economic status of Tanzania [30]. Similar results were also found in a Brazilian study where satisfaction levels with a rigid frame wheelchair design were reported to be 4.2 (high satisfaction level) [31].…”
Section: Discussionsupporting
confidence: 82%
“…Another similarity was female users being more satisfied with the wheelchair compared to men. In Tanzania the reported satisfaction levels with locally manufactured wheelchairs were higher compared to this study where customized wheelchairs were provided that can be contributed to the poor economic status of Tanzania [30]. Similar results were also found in a Brazilian study where satisfaction levels with a rigid frame wheelchair design were reported to be 4.2 (high satisfaction level) [31].…”
Section: Discussionsupporting
confidence: 82%
“…Without regular maintenance/repair services, wheelchairs in developing countries usually fail more quickly than their expected life span, which leads to adverse effects on social participation [71]. While more than half of participants in Tanzania were satisfied with the features of the wheelchairs, few were happy with follow-up services [3]. Similarly, a study in Zimbabwean found that wheelchair users showed high levels of dissatisfaction with wheelchair features, services, and the majority reported that wheelchairs did not provide effective mobility [78].…”
Section: Wheelchair Use In Low-resourced Settingsmentioning
confidence: 99%
“…A tendência de mudança da epidemiologia da lesão medular traumática diz respeito ao aumento gradual da idade média das pessoas, uma proporção maior de lesões relacionadas a quedas da própria altura e aumento das lesões cervicais e incompletas, especialmente entre os mais idosos (BÁRBARA-BATALLER et al, 2018;KUDO et al, 2019;MIRZAEVA et al, 2019;MITCHELL et al, 2020;SMITH et al, 2019). Estes estudos sugerem a necessidade de uma avaliação de risco multidimensional e intervenção multifatorial, especialmente para reduzir quedas e lesão medular em idosos.…”
Section: Discussionunclassified
“…Na avaliação de satisfação com a TA verificou-se que o nível de satisfação com a cadeira de rodas atingiu uma média maior que a prestação de serviço. Estes resultados estão alinhados com os dados apresentados por um estudo realizado na Tanzânia, quando os participantes ficaram satisfeitos com as características do recurso de TA, mas não com a prestação de serviços (AMOSUN; NDOSI; BUCHANAN, 2016). A TA impactou de forma positiva as necessidades de atividade e participação social (AMOSUN; NDOSI; BUCHANAN, 2016).…”
Section: Discussionunclassified